Implementasi Kebijakan: Apa, Mengapa dan Bagaimana - Haedar Akib (Jurnal Ilmiah Ilmu Administrasi Publik, 2010)
Policy implementation has gained substantial currency and popularity among teoriticians and pratitioners. Many now indicate an interest or involvement in research and discussion about such topic as policy implementation of poverty alleviation program or community development driven program, implementation of decentralization or local autonomy program, and implementation of strategic decision, etc. At the same time, perspectives, schools and program have been introduced and established. In spite of all this interest in policy implementation theories and practices, there is still no aggreement on what policy implementation model applicable to all kinds of development programs or projects, and to different sectors. This article will explain policy implementation concepts and their perspectives, models and measurement criteria with the contour or focus on what, why, and how policy implementation.   Kata Kunci: Apa, Mengapa dan Implementasi Kebijakan, Berbasis Pengetahuan.